Islet Product Characteristics and Factors Related to Successful Human Islet Transplantation From the Collaborative Islet Transplant Registry (CITR) 1999–2010. Issue 11 (2nd October 2014) - Balamurugan, A. N.; Naziruddin, B.; Lockridge, A.; Tiwari, M.; Loganathan, G.; Takita, M.; Matsumoto, S.; Papas, K.; Trieger, M.; Rainis, H.; Kin, T.; Kay, T. W.; et al.
<x xml:space="preserve">Abstract</x> The Collaborative Islet Transplant Registry (CITR) collects data on clinical islet isolations and transplants. This retrospective report analyzed 1017 islet isolation procedures performed for 537 recipients of allogeneic clinical islet transplantation in 1999–2010. This study describes changes in donor and islet isolation variables by era and factors associated with quantity and quality of final islet products. Donor body weight and BMI increased significantly over the period (p < 0.001). Islet yield measures have improved with time including islet equivalent (IEQ)/particle ratio and IEQs infused. The average dose of islets infused significantly increased in the era of 2007–2010 when compared to 1999–2002 (445.4 ± 156.8 vs. 421.3 ± 155.4 ×103 IEQ; p < 0.05). Islet purity and total number of β cells significantly improved over the study period (p < 0.01 and <0.05, respectively). Otherwise, the quality of clinical islets has remained consistently very high through this period, and differs substantially from nonclinical islets. In multivariate analysis of all recipient, donor and islet factors, and medical management factors, the only islet product characteristic that correlated with clinical outcomes was total IEQs infused. This analysis shows improvements in both quantity and some quality criteria of clinical islets produced over 1999–2010, and these parallel improvements in clinical outcomes over the same period.